(3JhVjM GdJPcQI ` aj Yde GdgjFIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO , jbhd (B: (3ef GdeYdhe Cf GdYdhe JJHGjf ai GdTQa HMSH JHGjf ehVhYGJgG hgh Yde gjFI GdCadGc hCf cJGH GdJPcQI ai gPG Gdaf GdefShH Edi GdWhSi Cf CcJH ajg TQMkG jPdd ef GddaX UhGHg s
(3BNQgG (B:s
(3aEf GdCYeGd HGdfjGJ , hHgG JLdH GdHQcGJ , hJfGd GdOQLGJ , hGdMeO ddg deHOY Gdcd hbO EJab aQGZi ef JCdja gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3HgG CTcGds
(3JYGhf YdjgG CcKQ ef fGSNs
(3fSNI QGHYI s
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGX s
(3cJHJ Hbde eged GdfbW CMjGfkG s
Keywords: (3Gdadcs